AgTFSI as p‐Type Dopant for Efficient and Stable Solid‐State Dye‐Sensitized and Perovskite Solar Cells. Issue 12 (25th September 2014) - Xu, Bo; Huang, Jing; Ågren, Hans; Kloo, Lars; Hagfeldt, Anders; Sun, Licheng
Abstract A silver‐based organic salt, silver bis(trifluoromethane‐sulfonyl)imide (AgTFSI), was employed as an effective p‐type dopant for the triarylamine‐based organic hole‐transport material Spiro‐MeOTAD, which has been successfully applied in solid‐state dye‐sensitized solar cells (ssDSCs) and perovskite solar cells (PSCs). The power conversion efficiencies (PCEs) of AgTFSI‐doped devices improved by 20 %, as compared to the device based on the commonly used oxygen doping both for ssDSCs and PSCs. Moreover, the solid‐state dye‐sensitized devices exposed to AgTFSI as dopant showed considerably better stability than those of oxygen doped, qualifying this p‐type dopant as a promising alterative for the preparation of highly efficient as well as stable ssDSCs and PSCs for the future.